2011
DOI: 10.1186/1477-7827-9-53
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of zona pellucida birefringence intensity during in vitro maturation of oocytes from stimulated cycles

Abstract: BackgroundThis study evaluated whether there is a relationship between the zona pellucida birefringence (ZP-BF) intensity and the nuclear (NM) and cytoplasmic (CM) in vitro maturation of human oocytes from stimulated cycles.ResultsThe ZP-BF was evaluated under an inverted microscope with a polarizing optical system and was scored as high/positive (when the ZP image presented a uniform and intense birefringence) or low/negative (when the image presented moderate and heterogeneous birefringence). CM was analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In addition, PLM has been used for the evaluation of the ZPB, which in humans has been associated with oocyte quality [116][117][118], although this is still under debate [119,120]. The few studies in cattle showed that a lower ZPB is related to high-quality oocytes and improved blastocyst development [121,122], whereas two studies in horses reported conflicting results, indicating beneficial effects of both low ZPB [123] and high ZPB [124].…”
Section: Assessment Of the Zona Pellucida Birefringencementioning
confidence: 99%
“…In addition, PLM has been used for the evaluation of the ZPB, which in humans has been associated with oocyte quality [116][117][118], although this is still under debate [119,120]. The few studies in cattle showed that a lower ZPB is related to high-quality oocytes and improved blastocyst development [121,122], whereas two studies in horses reported conflicting results, indicating beneficial effects of both low ZPB [123] and high ZPB [124].…”
Section: Assessment Of the Zona Pellucida Birefringencementioning
confidence: 99%
“…The ZP is a multilaminar glycoprotein coat that forms during oogenesis (34,35). At the molecular level, the ZP is composed of three layers that are composed of 4 protein filaments, ZP1, ZP2, ZP3, and ZP4 (12). However, the inner layer exhibits maximum birefringence with application of the PolScope (36).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the zona with high-order structured fibers might reflect the healthiness of an oocyte and its full oocyte maturation (nuclear and cytoplasmic) (12). In addition, in that study we observed that the percentage of a HB-ZP was significantly higher in the IVM oocytes than in vivo-matured ones, similar to findings reported by Omidi et al According to Braga et al and Petersen et al (12,37), the ZP birefringence is unaffected during IVM, and these findings confirm our results. We also observed that the fertilization rate after sperm injection (62.5%) in IVM oocytes was similar to those reported by earlier authors (39,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the selection of cattle oocytes by the presence of a PLM signal does not seem to offer improvement in IVP outcomes yet. In addition, PLM has been used for the evaluation of the ZPB, which in humans has been associated to oocyte quality [116][117][118], although it is still under debate [119,120]. The few studies in cattle have shown that a lower ZPB is related to high quality oocytes and improved blastocyst development [121,122], whereas two studies in horses have reported conflicting results, indicating beneficial effects of both low ZPB [123] and high ZPB [124].…”
Section: Evaluation Of the Meiotic Spindle And Zona Pellucida Birefrimentioning
confidence: 99%